Peran guru dalam mengatasi hilangnya attitude terhadap proses belajar siswa di MTs - Rayhan Ibnu Hajar Sumardi; Ani Sulianti; Didit Yulian Kasdrinato (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The research problem is caused by the lack of student attitude so that there are still students who carry out negative verbal and non-verbal bullying behavior. This study aims to describe the role of PPKn teachers in increasing attitudes to prevent negative actions, supporting and inhibiting factors and solutions for dealing with the inhibiting factors of PPKn teachers in increasing attitudes to prevent negative actions in MTs. Raudlatul Hasaniyah Probolinggo City. The method used is a qualitative descriptive approach. The subjects of this study included Civic Education teachers, students, principals and students. Data collection techniques in this study used observation, interview and documentation techniques. Data analysis techniques are carried out by data reduction, data display and data verification. From the research results obtained, namely the role of Civics teachers in increasing attitudes to prevent negative actions in MTs. Raudlatul Hasaniyah Probolinggo City is very important. PPKn teachers do their job very well. Efforts made by PPKn teachers in increasing attitudes to prevent negative actions are by a) forming good personalities in students b) always setting a good example directly to the rest c) being active in giving advice, direction and guidance to students d) making students think critically g) providing handling of cases of bullying. The driving factors for PPKn teachers in increasing attitudes to prevent negative actions are: a) there is cooperation from all school members, b) there are school rules, c) there is socialization from parties outside the school. The inhibiting factors are: 2) lack of awareness of students b) bad influence of association, c) lack of parental attention d) bad influence of social media.